A secure routing model based on distance vector routing algorithm - Wang, Bin (2013)
Distance vector routing protocols have been widely adopted as an efficient routing mechanism in current Internet, and any wireless networks. However, as is well-known, the existing distance vector routing protocols are insecure as it lacks of effective authorization mechanisms and routing updates aggregated from other routers. As a result, the network routing-based attacks become a critical issue which could lead to a more deteriorate performance than other general network attacks. To efficiently address this issue, this paper, through analyzing the routing model and its security aspect, and presents a novel approach on guaranteeing the routing security. Based on the model, we present the security mechanism including the message exchange and update message security authentication mechanism. The suggested approach shows that the security mechanism can effectively verify the integrity and validate the freshness of routing update messages received from neighbor nodes. In comparison with exiting mechanisms (SDV, S-RIP etc), the proposed model provides enhanced security without introducing significant network overheads and complexity.